Urban Rooftop Agriculture: Challenges to Science and Practice - Harada, Yoshiki; Whitlow, Thomas H. (Frontiers in Sustainable Food Systems, 2020)
Urban green infrastructure includes both natural inputs and artificial supplements, including irrigation, synthetic soil, and drainage layers. Green infrastructure aims to make cities more resilient and less dependent on outside resource inputs through more efficient use. Over the past 2 decades, these constructed ecosystems have expanded to include green roofs, elevated urban parks, and rooftop vegetable farms. This paper outlines opportunities and challenges for advancing the science of these constructed ecosystems with particular emphasis on rooftop agriculture. Although in concept rooftop agriculture could contribute to urban food security, water management, and biodiversity, research comparing design and management strategies across climate zones and regional economies is necessary to fully integrate ecological understanding into urban planning policy.